Chemophenetics as a Tool for Distinguishing Morphotypes of Annona emarginata (Schltdl.) H. Rainer - Ovile Mimi, Carolina [UNESP] (2021)
Annona emarginata (Annonaceae) has two morphological variations (A. emarginata ‘mirim’ and A. emarginata ‘terra-fria’). The species has agricultural value and produces specialized metabolites of pharmacological interest. The objective of this work was to analyze whether chemical and morphological differences contribute to differentiate A. emarginata ‘terra-fria’ from A. emarginata ‘mirim’, as chemophenetic variations of A. emarginata. The analysis of chemical compounds was based on the quantification, profile of root alkaloids and on the leaves volatile profile, together with morphometric analyses of the leaf blade. The samples were collected in three phenological stages (flowering, fruiting, and vegetative) at two places in São Paulo, Brazil. Differences in the composition of the alkaloid profile and leaf volatiles (in both places and in the three phenological stages) allowed us to separate the two morphotypes by multivariate statistical analysis. These differences agreed with the leaf blade morphology and flower color. This first chemophenetic report of A. emarginata demonstrates that, in addition to morphological variations, the specialized metabolism of roots and leaves can be phytochemical characters, which suggest the existence of at least morphochemotypes of A. emarginata.